Method and Psychological Effects on Learning Behaviors and Knowledge Creation in Quality Improvement Projects - Choo, Adrian S.; Linderman, Kevin W.; Schroeder, Roger G. (Management Science, 2007)
This study investigates two mechanisms of knowledge creation—one that is method driven and the other that is psychologically driven. Results show that the two mechanisms have different effects on the learning behaviors and knowledge created in Six Sigma projects. The method mechanism directly influences learning behaviors, while the psychological mechanism directly affects knowledge creation. The effects of both mechanisms on knowledge creation are complementary, yet independent. Findings suggest that the value of adhering to a method may lie in modifying the learning behaviors that subsequently create knowledge. When a firm adopts a quality program such as Six Sigma, the method and the degree of its adherence can shape how the firm innovates and creates knowledge.